Geophagia (dirt-eating) as a cause of anemia in children - Tevetoğlu, Fethi (The Turkish Journal of Pediatrics, 1961)
Geophagia (dirt-eating), a special form of pica, is a common phenomenon and may cause anemia in children. A review of the literature concerning this problem is briefly reported. 60 cases of geophagia with anemia, ranging in age from 11 1/2 months to 4 10/12 years, have been studied. The clinical and laboratory data and the treatment of this group are presented. The evidence presented would indicate that extensive dirt-eating is a cause of anemia in childhood.